Studying functional disulphide bonds by computer simulations - Gräter, Frauke; Li, Wenjin (Functional disulphide bonds, 2019)
Biochemical and structural data reveal important aspects of the properties and function of a protein disulphide bond. Molecular dynamics simulations can complement this experimental data and can yield valuable insights into the dynamical behavior of the disulphide bond within the protein environment. Due to the increasing accuracy of the underlying energetic description and the increasing computational power at hand, such simulations have now reached a level, at which they can also make quantitative and experimentally testable predictions. We here give an overview of the computational methods used to predict functional aspects of protein disulphides, including the prestress, protein allosteric effects upon thiol/disulphide exchange, and disulphide redox potentials. We then outline in detail the use of free-energy perturbation methods to calculate the redox potential of a protein disulphide bond of interest. In a step-by-step protocol, we describe the workflow within the MD suite Gromacs, including practical advice on the simulation setup and choice of parameters. For other disulphide-related simulation methods, we refer to resources available online.
Gesehen am 03.06.2020